Answer Set Programming Applied to Coreference Resolution and Semantic Similarity - (:unkn) unknown (SPRINGER HEIDELBERG, 2018)
We describe two research projects about solving problems in Computational Linguistics using Answer Set Programming, and we conclude with several lessons learned from these projects.
Keywords: ABDUCTION